A block polymer and its preparation method and its application in preparing polymer solid electrolyte and secondary battery

By introducing diblock or triblock copolymers into PVDF-based polymers, polymer solid electrolytes with microphase separation structures are solved, and the problems of low ion conductivity, low lithium ion migration number, and poor mechanical properties of polymer solid electrolytes in the prior art are solved, thereby achieving efficient electrochemical performance and mechanical performance improvement.

CN118772354BActive Publication Date: 2025-04-08SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410783756.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-18
Publication Date
2025-04-08
Estimated Expiration
2044-06-18

AI Technical Summary

Technical Problem

The existing polymer solid electrolytes have low ion conductivity at room temperature, low lithium ion migration number, poor mechanical properties, difficult to suppress the growth of metal lithium dendrites, and poor electrode interface compatibility.

Method used

By preparing a diblock or triblock copolymer and blending it with a PVDF-based polymer, a polymer solid electrolyte with macroscopic phase continuous and microphase separation is formed. The block copolymer contains segments that are well compatible with PVDF, as well as functional groups such as etheroxy groups, cyano groups, and sulfonic acid groups, which improves ionic conductance and lithium ion migration number.

Benefits of technology

It achieves high ion conductivity and lithium ion migration number, improves the cyclic stability and mechanical properties of polymer solid electrolytes, effectively inhibits the growth of metal lithium dendrites, and improves electrode interface compatibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118772354B_ABST
    Figure CN118772354B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of solid electrolytes, and discloses a block polymer and a preparation method thereof, and its application in the preparation of polymer solid electrolytes and secondary batteries. The present invention proposes for the first time an innovative design idea for polymer solid electrolytes: a polyvinylidene fluoride (PVDF)-based solid electrolyte with a double network structure. By copolymerizing structures such as fluorinated polyesters with other functional segments such as polyethers and polycarbonates to form diblock or triblock copolymers, and then blending with PVDF-based polymers, a macroscopically uniform but microphase-separated double continuous network structure is obtained, and a solid electrolyte is prepared after adding lithium salts. The PVDF phase can provide high mechanical support, and is beneficial to improving the solubility of lithium salts and fixing anions; the other phase is a diblock or triblock copolymer, which has segments such as fluorinated polyesters that are beneficial to the construction of a continuous phase structure, and contains polar segments such as polyethers and polycarbonates, which are beneficial to the rapid conduction of lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid electrolytes, and in particular relates to a block polymer and a preparation method thereof, and application thereof in the preparation of a polymer solid electrolyte and a secondary battery. Background Art

[0002] With the development of science and technology, energy issues have become increasingly prominent. Lithium-ion batteries are widely used in daily life due to their advantages such as high energy density, high reversibility, and low self-discharge. However, the liquid electrolyte commonly used in commercial lithium-ion batteries is highly volatile and flammable, and is prone to leakage or overheating in practical applications, leading to safety issues. In order to address safety issues and try to obtain higher energy density, solid-state batteries have received widespread attention from researchers.

[0003] Solid electrolytes can replace the electrolyte and separator in liquid batteries. The core of all-solid-state battery technology is to develop solid electrolytes that take into account high ionic conductivity, high lithium ion migration number, excellent mechanical properties, good electrochemistry, thermal stability and good interface compatibility. Although inorganic solid electrolytes have advantages in mechanical strength, room temperature ionic conductivity and chemical window, their poor processability and large solid / solid interface impedance limit their further application. Polymer solid electrolytes have many unique advantages: excellent mechanical properties, flexibility, easy processability and low cost, etc., so they are considered to be one of the most promising electrolytes in new high-energy storage devices. Classic polymer solid electrolytes are composed of a blend of polymers (such as PEO) and lithium salts (such as LiTFSI). Other polymer materials such as PVDF, PAN and PMMA have also been systematically studied as matrix materials for polymer solid electrolytes. At present, the more common defects or problems of polymer solid electrolytes include: (1) low ionic conductivity at room temperature; (2) low lithium ion migration number; (3) poor mechanical properties, making it difficult to inhibit the growth of metal lithium dendrites; (4) poor electrode interface compatibility, making it difficult to match high-voltage positive electrode materials. However, general modification or adjustment methods are difficult to take into account the synergistic improvement of the above properties, which restricts the development of polymer solid electrolytes in actual power battery and other application scenarios. The development of polymer electrolytes that are resistant to high voltage, have high room temperature ionic conductivity, and can inhibit lithium dendrite penetration is the current main research direction, but no substantial breakthroughs have been made. Summary of the invention

[0004] In order to solve the above problems, the purpose of the present invention is to provide a block polymer and a preparation method thereof and its application in the preparation of a polymer solid electrolyte and a secondary battery, so as to solve the problems of low ionic conductivity, low lithium ion migration number, poor mechanical properties, difficulty in inhibiting the growth of metal lithium dendrites, poor electrode interface compatibility and the like of existing polymer solid electrolytes at room temperature.

[0005] The present invention prepares a type of polymer solid electrolyte with macroscopic phase continuity and microphase separation by first preparing a type of diblock or triblock copolymer, and then blending it with a PVDF-based polymer. The block copolymer contains a segment that has good compatibility with PVDF, which is conducive to forming a uniform continuous phase; at the same time, it has segments containing functional groups such as ether oxygen, cyano, sulfonic acid, carbonate, carboxyl, urea, oligoether, etc., which is conducive to improving ion conductivity and lithium ion migration number. The introduction of the block copolymer reduces the crystallinity of the PVDF-based polymer, increases the proportion of the high-polarity β crystalline phase of the PVDF-based polymer, and is conducive to the further dissociation of high-concentration lithium salts. The PVDF-based polymer solid electrolyte with microphase separation shows high ionic conductivity and high lithium ion migration number. It is used to assemble Li||Li symmetrical batteries and has excellent cycle stability at room temperature (26°C).

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a type of block polymer, characterized in that the diblock or triblock polymer has the following structural formula:

[0008]

[0009] Wherein, R1 is selected from H or CH3;

[0010] R2 is independently selected from one or more of the following groups:

[0011]

[0012] R3 is selected from one or more of the following groups:

[0013]

[0014] n and m represent the number of repeating units of the polymerized monomer; n is any integer from 10 to 100,000, and m is any integer from 1 to 10,000.

[0015] The present invention also provides a method for preparing the block polymer, comprising the following steps:

[0016] (1) In an inert gas atmosphere, a polymer such as a polyether and an organic solvent are added to a reaction bottle, fully dissolved and mixed, and then a catalyst and an initiator are added and mixed, wherein the mass fraction of the catalyst is between 0.01 and 0.5%; the mass fraction of the initiator is between 0.1 and 10%, and the mixed solution is reacted and precipitated at a certain temperature to obtain a polyether macromolecular initiator;

[0017] (2) In an inert gas atmosphere, the polyether macromolecular initiator obtained in step (1) and an organic solvent are added to a Schlenk flask, and the mixture is fully dissolved and mixed. Then, a catalyst and a ligand are added, wherein the mass fraction of the catalyst is between 0.01% and 0.5%; the mass fraction of the initiator is between 0.1% and 10%, and then a monomer for block copolymerization is added, wherein the mass fraction of the monomer is between 5% and 80%;

[0018] (3) The pre-reaction mixed solution obtained in step (2) is stirred and reacted at a certain temperature. After the reaction is completed, the reaction mixture is precipitated in one or more solvents selected from methanol, acetone, ether, and tetrahydrofuran, and unreacted monomers and homopolymer impurities are washed away, and then precipitated with a n-hexane / ether mixed solution to obtain a diblock or triblock copolymer.

[0019] Preferably, in step (1), the structure of the first block copolymer is any one or more of the following structures:

[0020]

[0021] Preferably, in step (2), the structure of the second block copolymer is any one or more of the following structures:

[0022]

[0023] Preferably, in step (1), the organic solvent independently comprises 1,4-dioxane and dichloromethane; the catalyst comprises 4-dimethylaminopyridine and triethylamine; the initiator comprises 2-bromoisobutyryl bromide; the temperature of the first reaction is 0 to 100° C., and the time of the first reaction is 12 to 48 hours.

[0024] Preferably, in step (2), the organic solvent independently comprises 1,4-dioxane and dichloromethane; the catalyst comprises CuCl and CuBr; the initiator comprises pentamethyldiethylenetriamine and tris(2-dimethylaminoethyl)amine; the temperature of the second reaction is 30 to 150° C., and the time of the second reaction is 1 to 48 hours.

[0025] Preferably, in step (1) and step (2), the inert gas comprises helium or argon.

[0026] The present invention also provides an application of the block polymer in the preparation of a polymer solid electrolyte, characterized in that the preparation of the polymer solid electrolyte comprises the following steps: mixing a polyvinylidene fluoride polymer, a lithium salt, a block polymer and a solvent, and obtaining a polymer solid electrolyte through molding and drying.

[0027] Preferably, the polyvinylidene fluoride base includes PVDF or PVDF-HFP; the solvent includes dimethylformamide, dimethylacetamide, dimethyl sulfoxide or N-methyl-2-pyrrolidone; the amount ratio of polyvinylidene fluoride polymer, lithium salt, block polymer and solvent is 1-10:1-5:1-5:1-10; the mixing time is 1-24h; the molding is carried out in a polytetrafluoroethylene mold; the drying temperature is 50-80°C.

[0028] Preferably, the lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide salt, lithium trifluorosulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluoroborate, lithium difluoroborate, lithium tetrafluoroborate, lithium perchlorate and lithium bromide, and the lithium salt accounts for 10% to 80% of the total mass of the solid electrolyte.

[0029] The present invention also provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is a polymer solid electrolyte.

[0030] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0031] (1) This invention proposes for the first time an innovative design concept for polymer solid electrolytes: a PVDF-based polymer solid electrolyte with a microphase separation structure. By introducing another type of diblock or triblock copolymer into commercial PVDF or its copolymers (PVDF-HFP, etc.), a polymer with macrophase continuity and microphase separation is formed. The high molecular weight PVDF matrix ensures excellent film-forming properties and mechanical properties.

[0032] (2) The introduction of diblock or triblock copolymer components reduces the crystallinity of PVDF-based polymers, increases the proportion of high-polarity β-crystalline phase of PVDF-based polymers and the dielectric constant of copolymers, which is conducive to the further dissociation of high-concentration lithium salts; the fluorinated properties of PVDF can also react with the fluorinated anion TFSI. - or FSI - It has a high binding constant, which can not only increase the dissociation degree of lithium salt, but also significantly increase the migration number of lithium ions.

[0033] (3) The diblock or triblock copolymer contains chain segments that have good compatibility with PVDF, which is conducive to the formation of a uniform continuous phase; at the same time, it has chain segments containing functional groups such as ether groups, cyano groups, sulfonic acid groups, carbonate groups, carboxyl groups, urea groups, oligoethers, etc., which are used to construct lithium ion transmission channels, which is conducive to improving ion conductivity and increasing the lithium ion migration number.

[0034] (4) The PVDF-based polymer solid electrolyte with a microphase separation structure has an ionic conductivity of 2.3×10 at 30°C. -4S cm -1 , the ion transfer number is 0.59. The assembled Li||Li symmetric battery has a -2 The cycling is stable under the current density, showing a stable polarization voltage, and the symmetrical battery does not short-circuit.

[0035] (5) The block copolymer prepared by the method of the present invention has simple synthesis steps; the monomers and PVDF-based polymers used are commercial raw materials with low cost.

[0036] (6) The polymer-based solid electrolyte prepared by the method of the present invention is simple to process and can be prepared on a large scale by blade coating, tape casting or high-temperature hot pressing. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings in the following description are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0038] Figure 1 is the PEO-PTFEMA polymer in Example 1 1 HNMR spectrum;

[0039] Figure 2 is the GPC spectrum of the PEO-PTFEMA polymer in Example 1;

[0040] Figure 3 is the Fourier infrared spectrum of the PEO-PTFEMA polymer in Example 1;

[0041] Figure 4 is the X-ray diffraction spectrum of the PEO-PTFEMA polymer in Example 1;

[0042] Figure 5 is the PEO-PTFEA polymer in Example 2 1 HNMR spectrum;

[0043] Figure 6 is the PEO-POFPMA polymer in Example 3 1 H NMR spectrum;

[0044] Figure 7 is the PTFEMA-PEG-PTFEMA polymer in Example 4 1 H NMR spectrum;

[0045] Figure 8Graphs showing ionic conductivity of polymer solid electrolytes in Example 1, Comparative Example 1 and Comparative Example 2;

[0046] Fig. 9 This is a diagram of the electrochemical stability window of the polymer solid electrolyte in Example 1;

[0047] Fig.10 is the ion migration spectrum of the polymer solid electrolyte in Example 1;

[0048] Fig.11 The impedance diagram of the polymer solid electrolyte before and after polarization in Example 1;

[0049] Fig.12 is the ion migration spectrum of the polymer solid electrolyte in Comparative Example 1;

[0050] Fig.13 The impedance diagram of the polymer solid electrolyte before and after polarization in Comparative Example 1;

[0051] Fig.14 is the lithium-lithium symmetric spectrum of the polymer solid electrolyte in Example 1;

[0052] Fig.15 The diagram shows the bicontinuous phase structure and ion conduction mechanism of the solid electrolyte of the present invention. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below through specific examples. The following examples are only used to illustrate the present invention, but are not used to limit the scope of implementation of the present invention. All technical solutions obtained by equivalent replacement or equivalent transformation methods fall within the protection scope of the present invention. The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the field; the methods used in the present invention, unless otherwise specified, are all conventional methods in the field.

[0054] Example 1

[0055] The present invention provides a PEO-PTFEMA copolymer, and the structural formula of the PEO-PTFEMA copolymer is as follows:

[0056]

[0057] Among them, n is 300 and m is 200.

[0058] The preparation method of the PEO-PTFEMA copolymer of the present invention comprises the following steps:

[0059] (1) In an inert gas atmosphere, PEO polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide are mixed, reacted and precipitated at a certain temperature to obtain a PEO-Br macromolecular initiator;

[0060] (2) In an inert gas atmosphere, a PEO-Br macromolecular initiator, an organic solvent, CuBr, pentamethyldiethylenetriamine and TFEMA monomer are mixed, reacted and precipitated at a certain temperature to obtain a PEO-PTFEMA copolymer;

[0061] The structural formula of PEO polymer is The structural formula of PEO-Br macroinitiator is The structural formula of TFEMA monomer is

[0062] In step (1) and step (2) of the present invention, the organic solvent is independently 1,4-dioxane.

[0063] In step (1) of the present invention, the mass ratio of PEO polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and initiator is 1:100:0.005:0.01:1; the temperature of the first reaction is 40° C.; and the time of the first reaction is 24 hours.

[0064] In step (2) of the present invention, the mass ratio of PEO-Br macroinitiator, organic solvent, CuBr, pentamethyldiethylenetriamine and comonomer is 1:120:0.005:0.01:1; the comonomer is trifluoroethyl methacrylate (TFEMA); the temperature of the second reaction is 80°C; and the time of the second reaction is 24h.

[0065] In step (1) and step (2) of the present invention, the sedimentation includes a first sedimentation and a second sedimentation; the reagent used for the first sedimentation is ether, and the sedimentation is performed twice; the reagent used for the second sedimentation is n-hexane and ether (n-hexane: ether volume ratio is 1:1), and the sedimentation is performed twice to obtain pure diblock copolymers PEO-PTFEMA, which are named PEM1, PEM2, and PEM3 according to the different contents of PTFEMA.

[0066] In step (1) and step (2) of the present invention, the inert gas is helium.

[0067] The reaction equation of step (1) of the present invention is:

[0068]

[0069] The reaction equation of step (2) of the present invention is:

[0070]

[0071] The present invention also provides an application of the PEM block copolymer in the preparation of a polymer solid electrolyte. The preparation of the polymer solid electrolyte comprises the following steps: dissolving PVDF, lithium bistrifluoromethanesulfonyl imide (LiTFSI), a PEM block copolymer and a solvent in a DMF solution at a mass fraction ratio of 1:1:1, stirring at 60°C to form a uniform transparent solution, and sequentially molding and drying to obtain polymer solid electrolytes named PVDF / PEM1, PVDF / PEM2, and PVDF / PEM3.

[0072] Example 2

[0073] The present invention provides a PEO-PTFEA copolymer, and the structural formula of the PEO-PTFEA copolymer is as follows:

[0074]

[0075] Among them, n is 300 and m is 200.

[0076] The preparation method of the PEO-PTFEA copolymer of the present invention comprises the following steps:

[0077] (1) In an inert gas atmosphere, PEO polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide are mixed, reacted at 40° C. for 24 hours and then precipitated to obtain a PEO-Br macroinitiator;

[0078] (2) In an inert gas atmosphere, a PEO-Br macroinitiator, an organic solvent, CuBr, pentamethyldiethylenetriamine and TFEA monomer are mixed, reacted at 80° C. for 24 hours and then precipitated to obtain a PEO-PTFEA copolymer;

[0079] The structural formula of PEO polymer is The structural formula of PEO-Br macroinitiator is The structural formula of TFEA monomer is

[0080] In step (1) and step (2) of the present invention, the organic solvent is independently 1,4-dioxane.

[0081] In step (1) of the present invention, the mass ratio of PEO polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and initiator is 1:100:0.05:0.5:1.5.

[0082] In step (2) of the present invention, the mass ratio of PEO-Br macroinitiator, organic solvent, CuBr, pentamethyldiethylenetriamine and comonomer is 1:120:0.03:0.03:2; and the comonomer is 2,2,2-trifluoroethyl acrylate (TFEA).

[0083] In step (1) and step (2) of the present invention, the sedimentation includes a first sedimentation and a second sedimentation; the reagent used for the first sedimentation is diethyl ether, and the sedimentation is performed twice; the reagent used for the second sedimentation is n-hexane and diethyl ether (n-hexane: diethyl ether volume ratio is 1:1), and the sedimentation is performed twice to obtain a pure diblock copolymer and a pure PEO-PTFEA diblock copolymer.

[0084] In step (1) and step (2) of the present invention, the inert gas is helium.

[0085] The reaction equation of step (1) of the present invention is:

[0086]

[0087] The reaction equation of step (2) of the present invention is:

[0088]

[0089] Preparation of PEO-PTFEA block copolymer 1 H NMR spectrum Figure 5 shown.

[0090] Example 3

[0091] The present invention provides a PEO-POFPMA copolymer, and the structural formula of the PEO-POFPMA copolymer is as follows:

[0092]

[0093] Among them, n is 300 and m is 200.

[0094] The preparation method of the PEO-POFPMA copolymer of the present invention comprises the following steps:

[0095] (1) In an inert gas atmosphere, PEO polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide are mixed, reacted at 40° C. for 24 hours and then precipitated to obtain a PEO-Br macroinitiator;

[0096] (2) In an inert gas atmosphere, a PEO-Br macroinitiator, an organic solvent, CuBr, pentamethyldiethylenetriamine and OFPMA monomer are mixed, reacted at 80° C. for 24 hours and then precipitated to obtain a PEO-POFPMA copolymer;

[0097] The structural formula of PEO polymer is The structural formula of PEO-Br macroinitiator is The structural formula of OFPMA monomer is

[0098] In step (1) and step (2) of the present invention, the organic solvent is 1,4-dioxane.

[0099] In step (1) of the present invention, the mass ratio of PEO polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and initiator is 1:100:0.05:0.5:1.5.

[0100] In step (2) of the present invention, the mass ratio of PEO-Br macroinitiator, organic solvent, CuBr, pentamethyldiethylenetriamine and comonomer is 1:120:0.03:0.03:2; the comonomer is octafluoropentyl methacrylate (OFPMA).

[0101] In step (1) and step (2) of the present invention, the sedimentation includes a first sedimentation and a second sedimentation; the reagent used for the first sedimentation is diethyl ether, and the sedimentation is performed twice; the reagent used for the second sedimentation is n-hexane and diethyl ether (n-hexane: diethyl ether volume ratio 1:1), and the sedimentation is performed twice to obtain a pure PEO-POFPMA diblock copolymer.

[0102] In step (1) and step (2) of the present invention, the inert gas is argon.

[0103] The reaction equation of step (1) of the present invention is:

[0104]

[0105] The reaction equation of step (2) of the present invention is:

[0106]

[0107] Preparation of PEO-POFPMA block copolymers 1 H NMR spectrum Figure 6 shown.

[0108] Example 4

[0109] The present invention provides a PTFEMA-PEG-PTFEMA triblock copolymer, and the structural formula of the PTFEMA-PEG-PTFEMA copolymer is as follows:

[0110]

[0111] Among them, n is 300 and m is 200.

[0112] The preparation method of the PTFEMA-PEG-PTFEMA copolymer of the present invention comprises the following steps:

[0113] (1) In an inert gas atmosphere, PEG polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and 2-bromoisobutyryl bromide are mixed, reacted at 40° C. for 24 hours and then precipitated to obtain a PEG-Br macroinitiator;

[0114] (2) In an inert gas atmosphere, PEG-Br macroinitiator, organic solvent, CuBr, pentamethyldiethylenetriamine and TFEMA monomer were mixed, reacted at 80° C. for 24 h and then precipitated to obtain PTFEMA-PEG-PTFEMA copolymer;

[0115] The structural formula of PEG polymer is The structural formula of PEG-Br macroinitiator is The structural formula of TFEMA monomer is

[0116] In step (1) and step (2) of the present invention, the organic solvent is dichloromethane.

[0117] In step (1) of the present invention, the mass ratio of PEG polymer, organic solvent, 4-dimethylaminopyridine, triethylamine and initiator is 1:100:0.05:0.5:1.5.

[0118] In step (2) of the present invention, the mass ratio of PEG-Br macroinitiator, organic solvent, CuBr, pentamethyldiethylenetriamine and comonomer is 1:120:0.03:0.03:2; and the comonomer is trifluoroethyl methacrylate (TFEMA).

[0119] In step (1) and step (2) of the present invention, the sedimentation includes a first sedimentation and a second sedimentation; the reagent used for the first sedimentation is ether, and the sedimentation is performed twice; the reagent used for the second sedimentation is n-hexane and ether (n-hexane: ether volume ratio 1:1), and the sedimentation is performed twice to obtain a pure PTFEMA-PEG-PTFEMA triblock copolymer.

[0120] In step (1) and step (2) of the present invention, the inert gas is helium.

[0121] The reaction equation of step (1) of the present invention is:

[0122]

[0123] The reaction equation of step (2) of the present invention is:

[0124]

[0125] PTFEMA-PEG-PTFEMA triblock copolymer was prepared.

[0126] Comparative Example 1

[0127] A PVDF polymer blend solid electrolyte comprises the following preparation steps:

[0128] PVDF, PEO polymer and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in DMF solution at a mass fraction ratio of 1:1:1. Stir at 60°C until a uniform transparent solution was formed. Subsequently, the solution was slowly introduced into a polytetrafluoroethylene mold, part of the DMF solvent was volatilized in a dry environment, and then transferred to a vacuum drying oven for further drying. The resulting polymer solid electrolyte was named PVDF / PEO.

[0129] Comparative Example 2

[0130] A PVDF polymer blend solid electrolyte comprises the following preparation steps:

[0131] PVDF, PMMA polymer and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were dissolved in DMF solution at a mass fraction ratio of 1:1:1. Stir at 60°C until a uniform transparent solution was formed. Subsequently, the solution was slowly introduced into a polytetrafluoroethylene mold, part of the DMF solvent was volatilized in a dry environment, and then transferred to a vacuum drying oven for further drying. The resulting polymer solid electrolyte was named PVDF / PMMA.

[0132] Characterization and performance testing:

[0133] Depend on Figures 1 to 7 It can be seen that we have successfully prepared block copolymers and blended them with PVDF-based polymers to prepare polymer solid electrolytes. Figures 8 to 14 It can be seen that the physically blended solid electrolyte has excellent electrochemical properties.

[0134] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A block polymer characterized in that: The structural formula of diblock or triblock polymers is as follows: Wherein, R1 is selected from H or CH3; R2 is independently selected from one or more of the following groups: R3 is selected from one or more of the following groups: n and m represent the number of repeating units of the polymerized monomer; n is any integer from 10 to 100,000, and m is any integer from 1 to 10,000.

2. The method for preparing a block polymer according to claim 1, characterized in that: The method for preparing the block polymer comprises the following steps: (1) In an inert gas atmosphere, a polyether polymer and an organic solvent are added to a reaction bottle, and the mixture is fully dissolved and mixed. Then, a catalyst and an initiator are added and mixed, wherein the mass fraction of the catalyst is between 0.01 and 0.5%; the mass fraction of the initiator is between 0.1 and 10%, and the mixed solution is reacted and precipitated at a certain temperature to obtain a polyether macromolecular initiator; (2) In an inert gas atmosphere, the polyether macromolecular initiator obtained in step (1) and an organic solvent are added to a Schlenk flask, and the mixture is fully dissolved and mixed. Then, a catalyst and a ligand are added, wherein the mass fraction of the catalyst is between 0.01% and 0.5%; the mass fraction of the initiator is between 0.1% and 10%, and then a monomer for block copolymerization is added, wherein the mass fraction of the monomer is between 5% and 80%; (3) The pre-reaction mixed solution obtained in step (2) is stirred and reacted at a certain temperature. After the reaction is completed, the reaction mixture is precipitated in one or more solvents selected from methanol, acetone, ether, and tetrahydrofuran, and unreacted monomers and homopolymer impurities are washed away, and then precipitated with a n-hexane / ether mixed solution to obtain a diblock or triblock copolymer.

3. The method for preparing a block polymer according to claim 2, characterized in that: In the step (1), the structure of the first block copolymer is any one or more of the following structures:

4. The method for preparing a block polymer according to claim 2, characterized in that: In the step (2), the structure of the second block copolymer is any one or more of the following structures:

5. The method for preparing the block polymer according to claim 2, characterized in that: In the step (1), the organic solvents independently include 1,4-dioxane and dichloromethane; the catalysts include 4-dimethylaminopyridine and triethylamine; the initiator includes 2-bromoisobutyryl bromide; the temperature of the first reaction is 0 to 100° C., and the time of the first reaction is 12 to 48 hours.

6. The method for preparing the block polymer according to claim 2, characterized in that: In the step (2), the organic solvent independently comprises 1,4-dioxane and dichloromethane; the catalyst comprises CuCl and CuBr; the initiator comprises pentamethyldiethylenetriamine and tris(2-dimethylaminoethyl)amine; the temperature of the second reaction is 30 to 150° C., and the time of the second reaction is 1 to 48 hours.

7. Use of the block polymer prepared by the preparation method according to any one of claims 1 to 6 in the preparation of polymer solid electrolytes, characterized in that: The preparation of the polymer solid electrolyte comprises the following steps: mixing a polyvinylidene fluoride polymer, a lithium salt, a block polymer and a solvent, and performing molding and drying to obtain a polymer solid electrolyte.

8. The use according to claim 7, characterized in that: The polyvinylidene fluoride polymer includes PVDF or PVDF-HFP; the solvent includes dimethylformamide, dimethylacetamide, dimethyl sulfoxide or N-methyl-2-pyrrolidone; the mass ratio of the polyvinylidene fluoride polymer, lithium salt, block polymer and solvent is 1-10:1-5:1-5:1-10; the mixing time is 1-24 hours; the molding is carried out in a polytetrafluoroethylene mold; the drying temperature is 50-80°C.

9. Use of the block polymer according to claim 7 in preparing a polymer solid electrolyte, characterized in that: The lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide salt, lithium trifluorosulfonate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluoroborate, lithium difluoroborate, lithium tetrafluoroborate, lithium perchlorate and lithium bromide, and the lithium salt accounts for 10% to 80% of the total mass of the solid electrolyte.

10. A secondary battery, characterized in that: The invention comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the polymer solid electrolyte as claimed in claim 7.

Citation Information

Patent Citations

  • Polyethylene glycol (PEG)-b-polystyrene (PSt)-b-perfluorohexylethyl acrylate (PFHEA) and preparation method thereof

    CN102199261A

  • Polymer single-ion electrolyte and preparation method thereof

    CN103509153A